2009
DOI: 10.1017/s0007114509297236
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D deficiency and insufficiency in pregnant women: a longitudinal study

Abstract: Maternal vitamin D insufficiency is associated with childhood rickets and longer-term problems including schizophrenia and type 1 diabetes. Whilst maternal vitamin D insufficiency is common in mothers with highly pigmented skin, little is known about vitamin D status of Caucasian pregnant women. The aim was to investigate vitamin D status in healthy Caucasian pregnant women and a group of age-matched non-pregnant controls living at 54 -558N. Vitamin D insufficiency: Vitamin D supplementation: PregnancyVitamin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

13
147
5
11

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 211 publications
(176 citation statements)
references
References 28 publications
13
147
5
11
Order By: Relevance
“…37,38 Controversies exist on whether P-25OHD is affected by pregnancy per se. Holmes et al 26 found lower P-25OHD concentrations in women during their second and third trimester compared with non-pregnant controls, whereas Hillman et al 27 found no such pregnancy-induced decrease in P-25OHD. Neither do our data support an effect of pregnancy on P-25OHD concentrations, although our results are limited by the fact that most of our participants used vitamin D supplements.…”
Section: Discussionmentioning
confidence: 98%
“…37,38 Controversies exist on whether P-25OHD is affected by pregnancy per se. Holmes et al 26 found lower P-25OHD concentrations in women during their second and third trimester compared with non-pregnant controls, whereas Hillman et al 27 found no such pregnancy-induced decrease in P-25OHD. Neither do our data support an effect of pregnancy on P-25OHD concentrations, although our results are limited by the fact that most of our participants used vitamin D supplements.…”
Section: Discussionmentioning
confidence: 98%
“…This seasonal effect is correlated with the presence of a familial risk factor for MS [Sotgiu et al 2006] or with the phenotype HLA-DRB1 in Canada [Ramagopalan et al 2009a] but not in Finland [Saastoimanen et al 2012]. These results may be related to the vitamin D status of pregnant women [Willer et al 2005;Salzer et al 2010], since 25-OH-D serum levels are at their highest in autumn and their lowest in spring in the general population as well as in pregnant women [Hypponen and Power, 2007;Holmes et al 2009;Handel et al 2010a;Lewis et al 2010]. In line with this hypothesis, it may be consistent that in sunnier countries, that is, with less contrast between the seasons, no seasonal difference in the month of birth has been observed for MS risk [Givon et al 2012;Fragoso et al 2012].…”
Section: Genetic Risk Factors For Multiple Sclerosis Possibly Involvimentioning
confidence: 99%
“…1 Vitamin D status at birth and during early infancy, when breast milk is the predominant source of nutrition, is determined by maternal vitamin D status. 2,3 Contemporary population-and primary care-based studies of pregnant women have shown a high prevalence of serum 25(OH)D ,20 ng/mL in Asia (70%-96%), [4][5][6] Australia (10%-47%), [7][8][9][10] Europe (15%-44%), 11,12 the United Kingdom (49%-75%), [13][14][15] India (74%), 16 and the United States (37%). 17 Although less completely studied at the population level, in primary care-based studies from the United States, serum 25(OH)D ,20 ng/mL is present in 11% to 12% of infants.…”
mentioning
confidence: 99%